2013
DOI: 10.1264/jsme2.me13002
|View full text |Cite
|
Sign up to set email alerts
|

<i>Pseudosigmoidea ibarakiensis</i> sp. nov., a Dark Septate Endophytic Fungus from a Cedar Forest in Ibaraki, Japan

Abstract: A dark septate fungus of Pseudosigmoidea, Hyphomycetes, was recovered from forest soil in Ibaraki prefecture, Japan. The isolate is characterized by pale to brown conidia with up to 8 septa measuring 68–132 × 4–7.9 μm. It is also unique in producing conidia borne by long conidogenious cells in agar medium with or without water, compared to P. cranei, which must be immersed in water to sporulate. Morphological analysis indicated that the isolate is distinct from P. cranei and is described as a new species, P. i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 40 publications
3
16
2
1
Order By: Relevance
“…Similar to previous works on plant responses to inoculation with DSE fungi (Usuki and Narisawa, 2007 ; Diene et al, 2013 ; Mahmoud and Narisawa, 2013 ; Qin et al, 2017 ), the present study showed that inoculation with DSE fungi led to an increase in aboveground dry biomass of tomato plants supplied with an organic N source (finely ground C. ensiformis - 15 N). The same effect was not observed in plants treated with an inorganic N source (ammonium sulfate- 15 N).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to previous works on plant responses to inoculation with DSE fungi (Usuki and Narisawa, 2007 ; Diene et al, 2013 ; Mahmoud and Narisawa, 2013 ; Qin et al, 2017 ), the present study showed that inoculation with DSE fungi led to an increase in aboveground dry biomass of tomato plants supplied with an organic N source (finely ground C. ensiformis - 15 N). The same effect was not observed in plants treated with an inorganic N source (ammonium sulfate- 15 N).…”
Section: Discussionsupporting
confidence: 91%
“…Samples were observed and images were analyzed as described above. Symptoms were evaluated on scale of 0–3 (0: no visible symptoms; 1: light yellowing; 2: yellowing and late growth; 3: wilting or death) (Diene et al, 2013 ; Mahmoud and Narisawa, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…Usuki & Narisawa (2007) evaluated the ability of H. chaetospira to use different amino acids and inorganic N sources, and observed a significant increase in fungal dry mass in media modified with organic sources of the nutrient, compared with that supplemented with NH 4 NO 3 or without N. The same authors, while inoculating this fungus in B. campestris supplemented with the same N sources, found that inoculation promoted the use of all amino acids and NaNO 3 , with effects on plant growth. Similar results have been reported in the literature (Diene et al, 2013;Mahmoud & Narisawa, 2013).…”
Section: Dark Septate Endophytic Fungisupporting
confidence: 92%
“…In contrast, in cucumber (Cucumis sativus L.) inoculated with the DSE Pseudosigmoidea ibarakiensis and supplemented only with leucine, there was a 44% reduction in plant dry mass (Diene et al, 2013). However, in rice plants inoculated with DSE fungi, grown under controlled conditions and supplemented with NH 4 NO 3 , significant increments were observed for plant dry matter, N amino acid, soluble sugars, number of tillers, besides changes in NO 3absorption kinetic parameters (K m and V max ) (Vergara et al, 2018a).…”
Section: Dark Septate Endophytic Fungimentioning
confidence: 95%
“…Therefore, to our knowledge, this study is the first report involving DSEs in such environments. Three of the isolates used in the present study, i.e., H. velutinum isolate 41-1, V. simplex isolate Y34 and P. ibarakiensis isolate I.4-2-1, have already been reported to support plant growth under nutrient-deficient and other acidic pH conditions but not in contaminated conditions [30] , [31] , [32] . These results shed a light on a new field of use of these isolates.…”
Section: Discussionmentioning
confidence: 83%